Institutional mistrust and child vaccination coverage in Africa - Stoop, Nik; Hirvonen, Kalle; Maystadt, Jean-Francois (BMJ, 2021)
Despite considerable improvements in vaccination coverage over the last decade, half of the world’s unvaccinated and undervaccinated children are located in Africa. The role of institutional trust in explaining vaccination gaps has been highlighted in several qualitative reports but so far has only been quantified in a small number of high-income countries.